2019
DOI: 10.5603/fm.a2019.0019
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral giant and unilateral duplicated sphenoidal tubercle

Abstract: The sphenoidal tubercle (SphT), also known as pyramidal tubercle or infratemporal spine projects from the anterior end of the infratemporal crest of the greater sphenoidal wing. As it masquerades the lateral entrance in the pterygopalatine fossa it could obstruct surgical corridors or the access for anaesthetic punctures. The SphT is, however, an overlooked structure in the anatomical literature. During a routine cone beam computed tomography study in an adult male patient we found bilateral giant SphTs transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(25 reference statements)
0
1
1
Order By: Relevance
“…It is confused with the sphenoid spine in some studies [11,15]. It has been reported that the sphenoidal tubercle was found to be giant bony prominence in a case and it may pose an obstacle to surgical access to the skull base [11]. In this study, we did not identify any remarkable morphology in the sphenoidal tubercle, and the mean STS values on the right and left sides were found to be quite close to each other.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…It is confused with the sphenoid spine in some studies [11,15]. It has been reported that the sphenoidal tubercle was found to be giant bony prominence in a case and it may pose an obstacle to surgical access to the skull base [11]. In this study, we did not identify any remarkable morphology in the sphenoidal tubercle, and the mean STS values on the right and left sides were found to be quite close to each other.…”
Section: Discussioncontrasting
confidence: 40%
“…Another surgical reference point used in infratemporal fossa surgeries is a bony prominence located at the anterior end of the infratemporal crest, referred to as the sphenoidal tubercle in the literature. It is confused with the sphenoid spine in some studies [11,15]. It has been reported that the sphenoidal tubercle was found to be giant bony prominence in a case and it may pose an obstacle to surgical access to the skull base [11].…”
Section: Discussionmentioning
confidence: 99%